Avaliação do estágio de desenvolvimento da responsabilidade social no Banco Central do Brasil - Véras, Marcelo Lima (2009)
This study examines the corporate social responsibility (CSR) theme in Central Bank of Brazil (Bacen). The CSR movement is growing worldwide and it is related to values such as sustainability, ethics and transparency to the stakeholders. The study was performed in two parts. The first part consists of a bibliography research on the origins, the concept and the practice relating to CSR in the contemporary organizational environment. In the second part - field research - the Central Bank's Board of Directors and representatives of Ibase and Ethos Institute were interviewed and the content analysis method - a qualitative research method - was used in the interpretation of information obtained. The analysis of the interviews shows that the Board is receptive to the CSR development and that they consider the accomplishment of Central Bank's institutional mission fundamental in this process. The participation of the Bank's personnel and the incorporation of the CSR principles into the day-to-day practice are also considered necessary. Finally, one hundred indicators - based on the Ethos CSR Indicators - are proposed to evaluate the stage of development of social responsibility in Bacen on the following subjects: Values, Transparency and Governance; Internal Public; Natural Environment, Suppliers and Society. In summary, this study aims to contribute to the improvement of the knowledge of corporate social responsibility and the best practices in the public sector, particularly in Central Bank of Brazil.